Ritual soundings : women performers and world religions - Weiss, Sarah (New perspectives on gender in music., 2019)
This text documents ways in which women's performance practices engage with and localize world religions while creating opportunities for women's agency. This study draws on the rich resources of three disciplines: ethnomusicology, gendered studies of religion, and religious music studies. It is a meta-ethnography formed by comparisons among different ethnographic case studies. The work analyses women's performances at religious events in cultural settings spread across the world to demonstrate the pivotal roles women can play in localizing the practice of world religions, exploring moments in which performance allows women the agency to move, however momentarily, beyond culturally determined boundaries while revealing patterns that suggest unsuspected similarities in widely divergent religious contexts.